2009
DOI: 10.5580/21a7
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of microbial biota associated with rhizosphere of wheat (Triticum aestivum) during flowering stage and their plant growth promoting traits.

Abstract: Microbial biota associated with wheat rhizosphere during flowering-stage and their plant growth promoting traits was investigated. 16S rRNA gene sequencing was performed of the isolates, which were obtained on selective media. Isolates belonged to: alpha-proteobacteria, beta-proteobacteria, gamma-proteobacteria; Actinobacteria; Bacteroidetes and Firmicutes. Bacillus was the most dominant genus (34.7%) followed by Pseudomonas (14.4%). Among diazotrophs, Arthrobacter sp. (n=3), Cupriavidus sp. (n=3) and Stenotro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 26 publications
0
2
0
Order By: Relevance
“…Azospirillum species are broadly distributed ecologically and are associated with vast varieties of plants including wheat, rice, maize and several non-leguminous crops [26] Ensifer adharenes was reported during the year 2011-2012 but this taxon did not appear again in rest of the study and previously reported in wheat cultivated soil samples [27]. Similarly, Frankia is a filamentous bacteria found in symbiotic association with non-leguminous crop, observed during the second year of study [28]. Indole acetic acid producing bacteria Ideonella sp.…”
Section: Resultsmentioning
confidence: 72%
“…Azospirillum species are broadly distributed ecologically and are associated with vast varieties of plants including wheat, rice, maize and several non-leguminous crops [26] Ensifer adharenes was reported during the year 2011-2012 but this taxon did not appear again in rest of the study and previously reported in wheat cultivated soil samples [27]. Similarly, Frankia is a filamentous bacteria found in symbiotic association with non-leguminous crop, observed during the second year of study [28]. Indole acetic acid producing bacteria Ideonella sp.…”
Section: Resultsmentioning
confidence: 72%
“…Among the organic acids detected in the present study in soil solution, acetic acid was detected in relatively higher amounts followed by oxalic acid and citric acid. The presence of organic acids in the rhizosphere of different crops has been reported previously (Badri & Vivanco, 2009) and it has been found that rate of root exudates released by the plant roots influences microbial biota and activity in rhizosphere (Sachdev et al, 2009).…”
Section: Discussionmentioning
confidence: 72%